Bazaar of opportunities for new business development bridging networked innovation, intellectual property and business - Paasi, Jaakko. (Series on technology management, 2013)
Bazaar of Opportunities for New Business Development goes beyond the paradigm of open innovation and underlines the variety of opportunities that firms may have in innovation and new business development with external actors. This book shows readers that firms can interact, innovate, and do business with different known and unknown actors, both formally and informally, and use different levels of openness within interorganizational innovation processes. External actors, however, also mean additional risks for the firm that they should manage. The subtitle of book, Bridging Networked Innovation, Intellectual Property and Business, addresses the guidance and perspectives that the book will provide in order to better prepare the reader for innovation with external actors. Bazaar of Opportunities has a multidisciplinary approach to the subject, bringing innovation, business, legal and network management perspectives together. The findings are based on state-of-the-art practices of innovative firms in Europe, empirical data collected through interviews and case studies. Through this multidisciplinary approach and the empirical findings, the reader may gain insight on how to be successful in open and networked innovation.